Branding estratégico para la empresa Urco Asesores de Seguros - Sandoval Cañar, Dennis Javier (2024)
The general objective of this research was to develop a strategic branding plan with the purpose of improving the positioning of the brand in the sector, for the company Urco Asesores de Seguros, through a market study. The methodology was based on a descriptive study, with a mixed approach, bibliographic and field analysis. 4 samples were used, the first were 384 inhabitants of the city of Ambato as potential clients, the second were 35 business clients, the third were 3 direct suppliers and strategic allies and the fourth were 3 marketing and branding experts. In conclusion, develop a strategic branding plan to strengthen the brand identity and increase its visibility and competitiveness, attracting new customers and building loyalty among current ones.